2013
DOI: 10.1016/j.compositesa.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Damage analysis and fracture toughness evaluation in a thin woven composite laminate under static tension using infrared thermography

Abstract: International audienceThis work deals with the issue of damage growth in thin woven composite laminates subjected to tensile loading. The conducted tensile tests were monitored on-line with an infrared camera, and tested specimens were analysed using Scanning Electron Microscopy (SEM). Combined with SEM micrographs, observation of heat source fields enabled us to assess the damage sequence. Transverse weft cracking was confirmed to be the main damage mode and fiber breakage was the final damage leading to fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Another means to compare numerical and experimental results is through the extent of fiber failure before brutal propagation. Lisle et al proved that infrared emissions gave accurate estimations of damage growth in thin woven composite laminates subjected to tensile loading [50]. This method was adapted to notched laminated composites under tension.…”
Section: ''Large" Specimensmentioning
confidence: 99%
“…Another means to compare numerical and experimental results is through the extent of fiber failure before brutal propagation. Lisle et al proved that infrared emissions gave accurate estimations of damage growth in thin woven composite laminates subjected to tensile loading [50]. This method was adapted to notched laminated composites under tension.…”
Section: ''Large" Specimensmentioning
confidence: 99%
“…Following assumptions are assumed for the infrared image processing to obtain the heat source estimation: the temperature variation has no influence on the microstructure state, internal coupling sources are neglected, external heat does not depend on the time, coefficients ρ, C and conductivity tensor k (second order tensor) remain constant during the test and heat sources are assumed homogeneous through the thickness (low thickness compared to the length and width of the sample). Under these assumptions, the heat diffusion equation can be written as follows [9,10]:…”
Section: Heat Source Identificationmentioning
confidence: 99%
“…Acquired thermal fields can thus reveal and localize overheating related to degradation mechanisms (see works on carbon-epoxy of [5,6,7] and on glass-epoxy of [8]). Since temperature may be affected by external exchanges and/or by heat diffusion inside the material itself, the dissipation sources represent even a more accurate indicator of damage [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have also used passive infrared thermography to monitor the damage appearance and growth into composite materials. Battams and Dulieu‐Barton performed DIC and infrared thermography on the same surface of a [90,0] s laminate and have shown that transverse cracks can be observed with the two measurement techniques at intermediate strain rate (32 s −1 ).…”
Section: Introductionmentioning
confidence: 99%